2019
DOI: 10.1530/biosciprocs.1.012
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophic control of follicular development and function during the oestrous cycle of the ewe

Abstract: In the adult non-pregnant ewe the secretion of FSH is sufficient to ensure a continuous growth and development of antral follicles to 3-5 mm size at all times. Further development and increased secretion of oestradiol through the final 72 h to ovulation depends on adequate stimulation by LH. During anoestrus and the luteal phase of the cycle LH pulses occur too infrequently to stimulate sufficient oestradiol to evoke an LH surge. Moreover, during the luteal phase progesterone secreted by the corpus luteum not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
4
12
0
2
Order By: Relevance
“…Recent studies have shown that cultured granulosa cells from small sheep follicles do develop the ability to respond to LH in parallel with an ability to secrete oestradiol and that this responsiveness depends on FSH (B. K. Campbell, unpublished). Furthermore, while low doses of LH stimulated oestradiol synthesis, higher doses were inhibitory, which again closely parallels responses observed in vivo (Baird and McNeilly, 1981). From the evidence presented above, we conclude that the culture system for sheep and cattle granulosa cells that we have developed is physiological and that physiologically relevant inferences can be drawn from it.…”
Section: Intraovarian Control Of Follicledevelopmentsupporting
confidence: 80%
See 2 more Smart Citations
“…Recent studies have shown that cultured granulosa cells from small sheep follicles do develop the ability to respond to LH in parallel with an ability to secrete oestradiol and that this responsiveness depends on FSH (B. K. Campbell, unpublished). Furthermore, while low doses of LH stimulated oestradiol synthesis, higher doses were inhibitory, which again closely parallels responses observed in vivo (Baird and McNeilly, 1981). From the evidence presented above, we conclude that the culture system for sheep and cattle granulosa cells that we have developed is physiological and that physiologically relevant inferences can be drawn from it.…”
Section: Intraovarian Control Of Follicledevelopmentsupporting
confidence: 80%
“…Furthermore, complete removal of LH by passive immunization inhibits FSH-stimulated follicular development (McNeilly et al, 1991). Using a similar model in conjunction with the ovarian autotransplant model (Baird and McNeilly, 1981), we have confirmed and extended these results to show that LH pulses of low amplitude and frequency have little effect on the ability of FSH to stimulate the development of large antral follicles ( Fig. 1) and, in the absence of LH, these follicles remain critically dependent on FSH for gonadotrophic support ( Fig.…”
Section: Gonadotrophins Andfollicleselectionsupporting
confidence: 56%
See 1 more Smart Citation
“…This pulse pattern during the follicular phase is key to control of the reproductive cycle and facilitates the gonadotropin environment necessary to stimulate the pre-ovulatory E2 rise (Baird and McNeilly, 1981;Wallace et al, 1988;Campbell et al, 1990). The GnRH receptor works via a cascade starting with activation of phospholipase C hydrolyzing phosphatidylinositol 4,5-biphosphate to inositol 1,4,5-triphosphate and diacylgycerol (Limor et al, 1989;Perrin et al, 1989;Anderson et al, 1992).…”
Section: Hypothalamic-pituitary-ovarian Axismentioning
confidence: 99%
“…The surge in GnRH secretion subsequently stimulates a surge in LH from the anterior pituitary that results in ovulation (Baird and McNeilly, 1981).…”
Section: Follicular Phasementioning
confidence: 99%